Yttrium Vanadium Oxide–Poly(3, 4‐ethylenedioxythiophene) Composite Cathode Material for Aqueous Zinc‐Ion Batteries. Issue 9 (16th August 2021) - Kumankuma‐Sarpong, James; Guo, Wei; Fu, Yongzhu
Abstract: The development of metal ion‐intercalated active materials for excellent electrochemical performance in rechargeable aqueous zinc‐ion batteries (AZIBs) is challenging. The structure instability and intrinsic electrostatic repulsion of the lattice framework cause structural breakdown and low‐rate performance. In response to these problems, yttrium vanadium oxide–poly(3, 4‐ethylenedioxythiophene) (PEDOT@YVO) composite is reported as stable cathode material for AZIBs. The introduction of PEDOT in YVO nanorods improves the crystalline structure with an enlarged interplanar lattice spacing of 3.4 Å. The PEDOT@YVO composite electrode demonstrates effective electric conductivity and a higher initial specific capacity of 308.5 mAh g −1 than that (125.5 mAh g −1 ) of the pure YVO at 0.2 C rate. It also features a long‐term stable discharge–charge cycle performance of 4000 cycles with a capacity retention of 79.2% at 1C rate, better than YVO (29.4 mAh g −1 ). The oxygen vacancies and improved electrical conductivity of the composite account for the invigorated electrochemical performance. Consequently, this work reveals another avenue for constructing unique electrodes to enhance the electrochemical properties of AZIBs. Abstract : Yttrium vanadium oxide‐poly(3, 4‐ethylenedioxythiophene) (PEDOT@YVO) composite with an enlarged interplanar lattice spacing of 3.4 Å is synthesized to be a stable cathode material for aqueous zinc‐ion batteries (AZIBs). It demonstrates higher discharge capacities than the pure YVO at 0.2 C rate, and a long‐term stable discharge‐charge cycle performance of 4000 cycles with a capacity retention of 79.2%.